Diseño de una guía de juegos didácticos- pedagógicos para evaluar el nivel de conocimiento de los estudiantes de los octavos años de educación básica en el área de estudios sociales en el colegio “fiscal de ciclo básico popular y de producción Salcedo período 2012-2013 - Aviles Toapanta, Mónica Nataly (2013)
The purpose of this research is to determine the importance of the didactic pedagogic games use in the teaching-learning process of Social Studies in the students of Basic Cycle, therefore it is very important to design or innovative the strategies that are applied in the students’ evaluation. One of the demands and at the same time one of the most exciting challenges which teachers face nowadays is the approach of the educational process in a ludic way and non-monotonous. There is not school without innovations and there are not innovations without school. The teaching-learning process of Social Studies should be developed through pedagogic practices and the use of the didactic pedagogic games. The support of this kind of study involves goals from a very deep conviction: the improvement of the teaching-learning process which is the base of a new society. The essential objective of this project has been the design of a didactic-pedagogic games guide to evaluate the level of students' knowledge. The lack of practice of students from the place where the study was carried out stopped the use of new strategies and avoids to see teaching as something ludic, recreational and advantageous.